A magnitude weighting process for bistatic SAR digital beamforming implementation. Issue 8 (3rd August 2018) - Zhang, Heng; Shao, Yunfeng; Deng, Yunkai; Wang, Robert; Wang, Wei
ABSTRACT: Digital beamforming (DBF) technology splits the receiving antenna into multiple sub-apertures, which makes a promising candidate for imaging with a wide swath and high gain. Combining bistatic synthetic aperture radar (SAR) configuration with DBF technology provides more flexibility in designing microwave remote sensing missions, and which leads to a new bistatic SAR digital beamforming (BiSAR-DBF) approach. In this paper, a BiSAR-DBF implementation with magnitude weighting process is proposed. The effect of spatially variant heights and the corresponding modification are also analyzed. In the DBF experiment based on spaceborne-stationary bistatic configuration with TerraSAR-X as an illuminator has been successfully conducted in June 2013 by the Department of Space Microwave Remote Sensing System, Institute of Electronics, Chinese Academy of Sciences. Using the proposed method, the signal-to-noise (SNR) of BiSAR imagery is greatly improved.